PENINGKATAN MOTIVASI BERWIRAUSAHA DENGAN MELAKUKAN PELATIHAN PEMBUATAN YOGURT PADA GURU SD AL-ISLAH SURABAYA - Endah Budi Permana Putri; Rachma Rizqina Mardhotillah; Heni Agustina; Marselli Widya Lestari (Universitas Majalengka, 2022)
Knowledge related to entrepreneurship very necessary in pandemic conditions, where various sectors experience financial problems due decreased or loss of income sources. The way to solve problem is training entrepreneurship. This entrepreneurship training is one of the solutions that can be offered to realize this. Therefore, it is necessary to have other sources of income not only by hanging income from the main job, it is expected that teachers can have insight and entrepreneurial ability. One form of business that can be done from home is selling yogurt. Yogurt is a functional food that is rich in antioxidants, so it can increase the body's immunity if consumed regularly. The implementation community service is in the form of training to partners related to nutritional content, the benefits of consuming yogurt, how to make yogurt, packaging and marketing so that in future it is expected to be alternative entrepreneurship for Al-Islah Elementary School Teachers in Surabaya. The target outputs of this program are national journals/ proceedings, videos published activities, news of activities published in online/offline mass media and reports on improving skills and knowledge related to yogurt and its business opportunities